Visualities of Entrepreneurial Futures in Contemporary Ecuador - Hernández, Cristian-Germán; Bas, Enric (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article examines how visual representations of entrepreneurship in Ecuador shape the symbolic foundations of its imagined futures. Using a corpus of 120 images and applying Causal Layered Analysis, the study reveals a visual regime dominated by low-complexity production, ceremonial state presence, and moralized narratives of individual effort. These layers constrain the emergence of knowledge-based futures while naturalizing subsistence-oriented imaginaries. Yet, the expert panel identified early signals of a Transformation archetype grounded in collaboration, scientific capability, and creative experimentation. These findings highlight the cultural conditions necessary for reorienting Ecuador’s entrepreneurial trajectory.